Sleeping sites provide new insight into multiple central place foraging strategies of Tibetan macaques (Macaca thibetana) - Li, Bo-Wen; Li, Wen-Bo; Xia, Dong-Po; Zhang, Tong; Yang, Pei-Pei; Li, Jin-Hua (Frontiers in Ecology and Evolution, 2022)
Food resources, including food types, quantity, and quality, are the key factors that determine the survival and reproduction of wild animals. However, the most basic requirement is access to food. The choice of sleeping sites plays a crucial role in efficiently acquiring food and provides a useful starting point for studying foraging strategies. We collected data on sleeping site and foraging patch uses of wild Tibetan macaques (Macaca thibetana) in Huangshan, Anhui, China, from September 2020 to August 2021. We found that Tibetan macaques used 50 different sleeping sites, mostly located on cliffs, some of which they reused. Sleeping site altitude differed significantly according to season, with higher altitudes recorded in summer and winter. Tibetan macaques did not sleep as much as expected in the peripheral regions of their home range. The sleeping sites were often distributed in proximity to foraging patches, and there was a positive correlation between the use of sleeping sites and surrounding foraging patches. The utilization of foraging patches by Tibetan macaques is inclined towards the multiple central place foraging strategy. Our results provide supportive evidence for the proximity to food resource hypothesis and indicate the important role of sleeping sites in food resource utilization in Tibetan macaques.